Mothers' experiences and perceptions of breastfeeding peer support: a qualitative systematic review - Yuanyuan Yang; Huijuan Liu; Xiaoyi Cui; Jingwen Meng (BMC, 2024)
Abstract Background The global issue of low breastfeeding rates has been widely reported. Quantitative studies have shown the positive effects of peer support on breastfeeding. However, the experiences of mothers who receive breastfeeding peer support have been found to vary. To date, no systematic qualitative summary has been conducted to document the impact of peer support, nor to provide advice for its implementation from the perspective of breastfeeding mothers. This review aims to systematically synthesize qualitative findings on mothers' experiences of breastfeeding peer support to provide evidence for optimizing peer support services and ultimately enhancing their role in promoting breastfeeding. Methods PubMed, Embase, Cochrane Library, Ovid, Web of Science, CINAHL, China National Knowledge Infrastructure (CNKI), WanFang Datebase, VIP Database and Chinese Biomedical Database (CBM) were searched from the inception of each database until January 2023, to collect qualitative studies and mixed methods studies that included qualitative findings on mothers' experiences with breastfeeding peer support. The Joanna Briggs Institute Qualitative Assessment and Review Instrument (JBI-QARI) was used to extract data and evaluate the quality of the included articles. The meta-integration method was used to explain and integrate the research findings. The review process was carried out by two authors independently, and the disagreements were resolved through consensus. Results A total of 15 articles were included in the study, consisting of 13 qualitative studies and 2 mixed methods studies. The analysis identified four integrated themes: (1) obtaining psycho-emotional support; (2) acquiring knowledge and skills; (3) expectations for breastfeeding peer support; and (4) feeding perceptions and behavior change. It should be noted that the articles reviewed are in English and mostly originate from developed countries or regions. Therefore, the generalizability of the integrated findings to underdeveloped regions or non-English speaking countries may be limited. Conclusion Mothers perceived that peer support had a positive impact on breastfeeding. To improve the effectiveness of peer support in promoting breastfeeding, it is important to consider the individual needs of each mother. It is recommended that peer support services should be standardized in the future, including the accreditation, training, supervision, and management of peer supporters.